The northern California current on fire: consequences of a widespread and persistent anomalous pyrosome bloom - Richard D. Brodeur; Dylan G.E. Gomes; Douglas L. Draper; Elizabeth A. Daly; Samantha M. Zeman; Moira Galbraith; R. Ian Perry; James J. Ruzicka; Roxanne R. Robertson (Progress in Oceanography, 2026)

Social and Ecological Context Shape Biological Invasions in Complex Landscapes - George L. W. Perry; James M. R. Brock; Cameron B. Guy; Casey Hamilton; Finnbar Lee; Dion L. Pou; Elizabeth Williams; Erica A. H. Smithwick (Current Landscape Ecology Reports, 2025)

Play and peril: Displacement drivers and types across recreation motivations in crowding and wildfire-prone southern California national forests - Alyssa S. Thomas; Erin E. Budzyn; Elizabeth E. Perry; Brian A. Peterson; José J. Sánchez (Journal of Outdoor Recreation and Tourism, 2025)

Exposure to residential greenness, perceived stress, and depressive symptoms in a North American preconception cohort - Cameron J. Reimer; Mary D. Willis; Amelia K. Wesselink; Perry Hystad; Erin J. Campbell; Elizabeth E. Hatch; Kipruto Kirwa; Jaimie L. Gradus; Marco Vinceti; Lauren A. Wise; Marcia Pescador Jimenez (Environmental Research, 2024)

Ambient air pollution and rate of spontaneous abortion - Amelia K. Wesselink; Kipruto Kirwa; Perry Hystad; Joel D. Kaufman; Adam A. Szpiro; Mary D. Willis; David A. Savitz; Jonathan I. Levy; Kenneth J. Rothman; Ellen M. Mikkelsen; Anne Sofie Dam Laursen; Elizabeth E. Hatch; et al. (Environmental Research, 2024)

Reprint of: COVID-19 messaging in U.S. state parks: Extensions of the outdoor recreation strategies and practices framework unmasked by the pandemic - Elizabeth E. Perry; Kimberly J. Coleman; Tatiana A. Iretskaia; Jordan M. Baer; Liesl F. Magnus; Peter R. Pettengill (Journal of Outdoor Recreation and Tourism, 2023)

Park Visitors’ Place Attachment and Climate Change-related Displacement: Potential Shifts in Who, Where, and When - Elizabeth E. Perry; Xiao Xiao; John M. Nettles; Tatiana A. Iretskaia; Robert E. Manning (Environmental Management, 2021)

Attendance and nursing patterns of harp seals in the harsh environment of the northwest Atlantic - Elizabeth A. Perry; Garry B. Stenson; Alejandro D. Buren (Polar Biology, 2017)

Psychiatric safety of ketamine in psychopharmacology research - Edward B. Perry; Joyce A. Cramer; Hyun-Sang Cho; Ismene L. Petrakis; Laurence P. Karper; Angelina Genovese; Elizabeth O’Donnell; John H. Krystal; D. Cyril D’Souza (Psychopharmacology, 2007)

DNA fingerprinting evidence of nonfilial nursing in grey seals - ELIZABETH A. PERRY; DARYL J. BONESS; ROBERT C. FLEISCHER (Molecular Ecology, 1998)
We tested the hypothesis that kin selection may play a role in fostering behaviour in grey seals. Fostering frequency varied among three colonies, ranging from 3% to 28%. Band‐sharing coefficients (S) of DNA fingerprints, from two multilocus probes, were used to predict relatedness ( r ). Mean r did not differ between foster mother‐pup pairs and the expected r = 0 for presumed unrelated female‐pup pairs. Likewise, mean r between fostered and filial pups compared to r between presumed unrelated pups within the same beaches did not differ. Mean S values of presumed unrelated pups on different beaches within the two smallest colonies were indistinguishable, indicating that there is not increased variation in relatedness in small colonies. These results suggest that kin selection does not play a significant role in the maintenance of grey seal fostering behaviour.